Detailed Processes and Potential Mechanisms of Pliocene Salty Lake Evolution in the Western Qaidam Basin - Su, Qingda; Riegel, Hannah; Gong, Lisha; Heermance, Richard; Nie, Junsheng (Frontiers in Earth Science, 2021)
Hyperarid climate and salty lakes prevail in the current Qaidam Basin, but this basin was once a large paleolake until the early Quaternary. However, its evolution history and relationship with climate and tectonics are still elusive. Here we present detailed stratigraphic descriptions combined with total organic carbon content and weight ratio of organic carbon to total nitrogen records from fluvio-lacustrine sediments in the western Qaidam Basin to infer how the lake evolved during the late Pliocene-early Pleistocene. These data reveal a drying trend since 3.3 Ma, which we attribute to low latitude forcing and/or local tectonic activities. However, this trend was interrupted during 2.84-2.48 Ma, in which climate wetting was observed. We attribute the climate wetting during 2.84-2.48 Ma to intensified East Asian summer monsoon as is documented by the Chinese Loess Plateau records. Halite and gypsum content increased dramatically after 2.48 Ma, indicating the formation of salty lake in the western Qaidam Basin. These data improve our understanding of the detailed processes of Qaidam aridification and its potential forcing mechanisms.